Transcriptome analyses of ovarian stroma: tunica albuginea, interstitium and theca interna. Issue 6 (June 2019) - Hummitzsch, Katja; Hatzirodos, Nicholas; Macpherson, Anne M; Schwartz, Jeff; Rodgers, Raymond J; Irving-Rodgers, Helen F
Abstract : The ovary has specialised stromal compartments, including the tunica albuginea, interstitial stroma and theca interna, which develops concurrently with the follicular antrum. To characterise the molecular determinants of these compartments, stroma adjacent to preantral follicles (pre-theca), interstitium and tunica albuginea were laser microdissected ( n  = 4 per group) and theca interna was dissected from bovine antral follicles ( n  = 6). RNA microarray analysis showed minimal differences between interstitial stroma and pre-theca, and these were combined for some analyses and referred to as stroma. Genes significantly upregulated in theca interna compared to stroma included INSL3, LHCGR, HSD3B1, CYP17A1, ALDH1A1, OGN, POSTN and ASPN . Quantitative RT-PCR showed significantly greater expression of OGN and LGALS1 in interstitial stroma and theca interna versus tunica and greater expression of ACD in tunica compared to theca interna. PLN was significantly higher in interstitial stroma compared to tunica and theca. Ingenuity pathway, network and upstream regulator analyses were undertaken. Cell survival was also upregulated in theca interna. The tunica albuginea was associated with GPCR and cAMP signalling, suggesting tunica contractility. It was also associated with TGF-β signalling and increased fibrous matrix. Western immunoblotting was positive for OGN, LGALS1, ALDH1A1, ACD and PLN with PLN and OGN highly expressed in tunica and interstitial stroma (each n  = 6), but not in theca interna from antral follicles ( n  = 24). Immunohistochemistry localised LGALS1 and POSTN to extracellular matrix and PLN to smooth muscle cells. These results have identified novel differences between the ovarian stromal compartments.